Crowding-In and Crowding-Out Effects of Recurrent and Capital Expenditure on Human Capital Development in Nigeria - Edeme, Richardson Kojo; Nkalu, Nelson C (Asian Development Policy Review, 2016)
It has been argued that public expenditure on education and health is a veritable tool in improving human capabilities. Expenditure on these sectors is categorized into recurrent and capital. While capital expenditure can go a long way in enhancing the productivity capacity, recurrent expenditure is for non-productive activities. Available statistics however shows that in Nigeria, emphasis has been on recurrent expenditure at the detriment of capital expenditure. This study therefore employed multiple regression to ascertain how this pattern of expenditure crowd-in and crowd-out human capital development in Nigeria using capital and recurrent expenditure on education and health. The estimated models reveal that both capital and recurrent expenditure crowd-in and crowd-out human capital development. This outcome therefore suggests a new expenditure framework that refocuses more on capital expenditure than recurrent expenditure.